2009
DOI: 10.1017/s0031182009991533
|View full text |Cite|
|
Sign up to set email alerts
|

Triggering and modulation of the host-parasite interplay byEchinococcus multilocularis: a review

Abstract: S U M M A R YAs more facts emerge regarding the ways in which E. multilocularis-derived molecules trigger the host immune response and modulate the host-parasite interplay, it becomes possible to envisage how the parasite can survive and proliferate in its intermediate host, while in other hosts it dies out. Through effects on cells of both the innate and adaptive arms of the immune response, E. multilocularis can orchestrate a range of outcomes that are beneficial not only to the parasite, in terms of facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 104 publications
2
28
0
Order By: Relevance
“…A similar increase of susceptibility, associated with a decrease of delayed type hypersensitivity was also observed in E. multilocularis infected mice treated with ciclosporin, which interferes in IL-2 production by Tcells (Liance et al, 1992). Principally, upon experimental infection, immunocompetent mice elicit a cell-mediated immune response, which is so far inefficient as it impairs, but does not inhibit, the proliferation of the metacestode (Dai et al, 2004;Mejri et al, 2010). It has been shown that the type of the primary immune response toward infection, initially Th1-oriented, got progressively Th2-oriented (Mejri et al, 2011a) during the progressive growth of the metacestode, leading to the chronic stage of AE.…”
Section: Biology and Immunology Of Susceptibility Versus Resistance Isupporting
confidence: 56%
“…A similar increase of susceptibility, associated with a decrease of delayed type hypersensitivity was also observed in E. multilocularis infected mice treated with ciclosporin, which interferes in IL-2 production by Tcells (Liance et al, 1992). Principally, upon experimental infection, immunocompetent mice elicit a cell-mediated immune response, which is so far inefficient as it impairs, but does not inhibit, the proliferation of the metacestode (Dai et al, 2004;Mejri et al, 2010). It has been shown that the type of the primary immune response toward infection, initially Th1-oriented, got progressively Th2-oriented (Mejri et al, 2011a) during the progressive growth of the metacestode, leading to the chronic stage of AE.…”
Section: Biology and Immunology Of Susceptibility Versus Resistance Isupporting
confidence: 56%
“…Furthermore, the chemical composition of cyst fluid was discussed in some detail (Neisser, 1877). Recent developments of the immunobiology of the Echinococcus infection are described in previous reviews (e.g., Heath, 1995;Lightowlers and Gottstein, 1995;Gottstein and Hemphill, 2008;Mejri et al, 2010;Siracusano et al, 2012;Zhang et al, 2012) and in Chapter "Immunology...".…”
Section: Echinococcosis In Humansmentioning
confidence: 99%
“…Within the liver of the intermediate host, the oncosphere then undergoes a metamorphosis toward the bladder-like metacestode larval stage which grows infiltratively, like a malignant tumor, into the surrounding host tissue. During this process, the early Th1 response is gradually replaced by a Th2 response, dominated by interleukin (IL)-5 and IL-10 [4]. AE has a high case-fatality rate and is associated with severe morbidity.…”
Section: Introductionmentioning
confidence: 99%